The course of heart failure development and mortality in rats with volume overload due to aorto-caval fistula - Melenovský, Vojtěch; Škaroupková, Petra; Beneš, Jan; Torresová, Věra; Kopkan, Libor; Červenka, Luděk (Kidney & blood pressure research, 2012)
BACKGROUND: There are only few studies documenting the long-term outcome of aorto-caval fistula (ACF) in rats, a model of volume overload heart failure (HF). The aim of the present study was to describe HF-related morbidity and mortality, and to examine the relation between cardiac hypertrophy and survival. METHODS: Adult male Wistar rats underwent needle ACF or sham operation and 71 animals surviving the acute procedure with patent ACF were followed for 52 weeks. RESULTS: By the end of the study, 72% of the ACF animals deceased and 82% developed HF signs. Of the HF rats, 65% died (median: 3 weeks after HF onset). Before death, body weight increased by 9% followed by a final drop. 28% ACF rats died suddenly, without preceding HF. Sudden death occurred earlier and in the rats with a trend to larger hearts (p = 0.07). In the whole ACF cohort, heart weight (heart weight/body weight ratio) was inversely associated with the length of survival (r = -0.51, p < 0.001). CONCLUSION: The median survival of ACF Wistar rats is 43 weeks, longer than reported in other rat strains. Increased heart weight is associated with higher mortality and a significant number of animals die suddenly.
Keywords: Animals; Rats, Wistar; Heart Failure; srdeční selhání; vena cava inferior; Cardiomegaly; arteriovenózní píštěl; míra přežití; Male; aorta abdominalis; krysa rodu Rattus; Survival Rate; Vena Cava, Inferior; kardiomegalie; zvířata; mužské pohlaví; Arteriovenous Fistula; Aorta, Abdominal; Rats; potkani Wistar